2006
DOI: 10.1186/ar1952
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We investigated lipid profiles and lipoprotein modification after immuno-intervention in patients with early rheumatoid arthritis (ERA). Fifty-eight patients with ERA who met the American College of Rheumatology (ACR) criteria were included in the study. These patients had disease durations of less than one year and had not had prior treatment for it. Smokers or patients suffering from diabetes mellitus, hypothyroidism, liver or kidney disease, Cushing's syndrome, obesity, familiar dyslipidemia and those recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(49 citation statements)
references
References 43 publications
6
40
0
2
Order By: Relevance
“…In our study, the RA activity (DAS) was significantly high among RA patients with dyslipidemia (p=0.02). This is consistent with results of Georgiadis et al study in Greece 50 .…”
Section: Resultssupporting
confidence: 83%
“…In our study, the RA activity (DAS) was significantly high among RA patients with dyslipidemia (p=0.02). This is consistent with results of Georgiadis et al study in Greece 50 .…”
Section: Resultssupporting
confidence: 83%
“…A recent meta-analysis found that methotrexate use was associated with 21% fewer CV events (Figure 1)(40). Methotrexate does not appear to alter lipid profiles (41), and there is insufficient evidence about its effects on insulin resistance, hypertension or atherosclerotic plaque burden. Nevertheless, the apparent benefit of methotrexate in reducing heart disease risk in RA, and the strong evidence that CRP is a risk factor for heart disease, led to the development of a large randomized trial (http://ClinicalTrials.gov identifier: NCT01594333) designed to determine whether low dose methotrexate reduces heart disease risk in post-MI patients who have metabolic syndrome or diabetes mellitus (42).…”
Section: Effect Of Ra Therapies On CV Risk In Ramentioning
confidence: 99%
“…Research over the past decade has demonstrated increased CV risk in patients with rheumatoid arthritis (RA) versus non-RA subjects (57). However, the association between lipid levels and CV risk in RA appears to be more complex than in the general population, with systemic inflammation being a potential important contributor to changes in lipid profile (8).…”
Section: Introductionmentioning
confidence: 99%